Nitrate reductase is required for sclerotial development and virulence of Sclerotinia sclerotiorum - Wei, Junjun; Yao, Chuanchun; Zhu, Zonghe; Gao, Zhimou; Yang, Guogen; Pan, Yuemin (Frontiers in Plant Science, 2023)
Sclerotinia sclerotiorum, the causal agent of Sclerotinia stem rot (SSR) on more than 450 plant species, is a notorious fungal pathogen. We functionally characterized a S. sclerotiorum nitrate reductase (SsNR) using RNAi technology. SsNR-silenced mutants showed abnormity in mycelia growth, sclerotia formation, and infection cushion formation reduced virulence on rapeseed and soybean and decreased oxalic acid production. SsNR-silenced mutants are more sensitive to abiotic stresses such as Congo Red, SDS, H2O2, and NaCl. The expression levels of pathogenicity-related genes SsGgt1, SsSac1, and SsSmk3 are down-regulated in SsNR-silenced mutants, while SsCyp is up-regulated. These results indicate that SsNR is important for S. sclerotiorum during growth, reproduction, and infection.